2019
DOI: 10.1186/s13075-019-1907-x
|View full text |Cite
|
Sign up to set email alerts
|

Switch from reference etanercept to SDZ ETN, an etanercept biosimilar, does not impact efficacy, safety, and immunogenicity of etanercept in patients with moderate-to-severe rheumatoid arthritis: 48-week results from the phase III, randomized, double-blind EQUIRA study

Abstract: Background Sandoz etanercept (SDZ ETN; GP2015) is an etanercept biosimilar with equivalent efficacy and comparable safety and immunogenicity to reference etanercept (ETN) in patients with moderate-to-severe chronic plaque-type psoriasis. Methods EQUIRA was a phase III, double-blind study conducted in patients with moderate-to-severe rheumatoid arthritis and inadequate response to disease-modifying anti-rheumatic drugs. Eligible patients were randomized 1:1 to receive su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 19 publications
(19 reference statements)
0
28
0
2
Order By: Relevance
“…The improvement with GP2017 was maintained after switching at week 48. 50 In the EQUIRA study, the mean change from baseline in the FACIT-fatigue score at week 24 was 9.45 in the biosimilar GP2015 group and 11.82 in the etanercept group. Furthermore, no difference in FACIT-fatigue score was reported after switching to GP2015.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The improvement with GP2017 was maintained after switching at week 48. 50 In the EQUIRA study, the mean change from baseline in the FACIT-fatigue score at week 24 was 9.45 in the biosimilar GP2015 group and 11.82 in the etanercept group. Furthermore, no difference in FACIT-fatigue score was reported after switching to GP2015.…”
Section: Resultsmentioning
confidence: 99%
“…The EQUIRA study 50 , 54 aimed demonstrated similar efficacy and comparable safety and immunogenicity profile of GP2015 (Erelzi ® ; Sandoz GmbH, Kundl, Austria) to etanercept (Enbrel ® ; Immunex Corporation, Thousand Oaks, CA, USA) at week 24 in patients with moderate-to-severe RA who had an inadequate response to either synthetic or biologic DMARDs. Improvements from baseline in HAQ-DI and scores were comparable between GP2015 and etanercept groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biosimilar drugs can be approved for use in all indications held by the originator biologic by extrapolation of efficacy and safety data from at least one indication of the originator and with adequate scientific justification, that is, without direct comparative clinical studies in all indications [22]. Regarding switching from an originator product to a biosimilar, numerous published biosimilar studies have reported no safety or efficacy concerns even though not all regulatory guidelines require collection of such data [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%